The effectiveness of emotion regulation group training in reducing depression, anxiety, and stress symptoms in women during pregnancy - Ameli, Samira; Aslzaker , Maryam; Salehpour, Saghar; Jafari , Mahdi (Researcher Bulletin of Medical Sciences, 2022)
Background: Pregnancy and childbirth is a natural function but it is also a stressful and critical period that increases women’s vulnerability to psychological problems and also increases the mental health problems of the woman and her fetus, so they need interventions to improve maternal health during this time. This study investigated the effectiveness of emotion regulation group training in reducing depression, anxiety, and stress symptoms in women during pregnancy and postpartum. Materials and Methods: This quasi-experimental study had a pre-test, post-test and follow-up (2 months follow after delivery). The study population consisted of 31 pregnant women who were randomly divided into intervention (n = 15) and control (n = 16) groups. The Depression, Anxiety and Stress Questionnaire (DASS-21) was used in this study. Eight sessions of emotion regulation group training were administered to the intervention group and the control group received information about pregnancy and childbirth during 4 sessions. After intervention and also two months after delivery, the questionnaires were completed again. The results of the scales were analyzed by SPSS software using repeated measures analysis of variance. Results: The data analysis showed that depression, anxiety and stress in the intervention group are decreasing from pre-test to post-test and follow-up significantly more than control group. Conclusion: According to the results of this study, emotion regulation group training can be effective in reducing of depression, anxiety and stress symptoms in pregnant women.